2018
DOI: 10.1080/13607863.2018.1501661
|View full text |Cite
|
Sign up to set email alerts
|

Partners’ adjustment to older workers’ retirement: testing the role of preretirement expectations in a 10-year panel study

Abstract: Objectives: Retirement is not only an important later-life transition for the retiring individual, but also for his or her life partner. This study aims to improve our understanding of the partner's adjustment to the retirement of the older worker, by paying attention to the multidimensional nature of adjustment, and by examining to what extent preretirement expectations are predictive of postretirement experiences. Well-established adjustment predictorsi.e. preretirement resources and characteristics of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This study found that negative pre-retirement expectations about the consequences of retirement for leisure activities, social contacts and status predicted difficulties in adjusting to retirement. In a further study, negative pre-retirement expectations about post-retirement life in the domains of finances, relationship and shared leisure time, predicted difficulties postretirement for the partner of the person retiring (Damman et al, 2018). Though one study refers to the person retiring and the second to the partner, they suggest that if people have negative views about retirement then this could become a self-fulfilling prophecy.…”
Section: Pre-retirement Attitudes and Retirement Adjustmentmentioning
confidence: 89%
See 3 more Smart Citations
“…This study found that negative pre-retirement expectations about the consequences of retirement for leisure activities, social contacts and status predicted difficulties in adjusting to retirement. In a further study, negative pre-retirement expectations about post-retirement life in the domains of finances, relationship and shared leisure time, predicted difficulties postretirement for the partner of the person retiring (Damman et al, 2018). Though one study refers to the person retiring and the second to the partner, they suggest that if people have negative views about retirement then this could become a self-fulfilling prophecy.…”
Section: Pre-retirement Attitudes and Retirement Adjustmentmentioning
confidence: 89%
“…(with responses ranging from 1 for a large drop to 5 for a very small drop in income) which is a more objective measure of financial circumstances. Another study from the Netherlands found that, among the partners of retirees, expectation of post-retirement financial problems predicted problems with retirement adjustment (Damman et al, 2018). These findings indicate that people's perceptions of their financial circumstances and their expectations of their future financial circumstances impact on their sense of retirement adjustment.…”
Section: Financial Circumstances Retirement Expectations and Adjustmentmentioning
confidence: 93%
See 2 more Smart Citations